Paramedics delivering palliative and end-of-life care in community-based settings: A systematic integrative review with thematic synthesis. (March 2022) - Juhrmann, Madeleine L; Vandersman, Priyanka; Butow, Phyllis N; Clayton, Josephine M
Background: There is a growing demand for community palliative care and home-based deaths worldwide. However, gaps remain in this service provision, particularly after-hours. Paramedicine may help to bridge that gap and avoid unwanted hospital admissions, but a systematic overview of paramedics' potential role in palliative and end-of-life care is lacking. Aim: To review and synthesise the empirical evidence regarding paramedics delivering palliative and end-of-life care in community-based settings. Design: A systematic integrative review with a thematic synthesis was undertaken in accordance with Whittemore and Knafl's methodology. Prospero: CRD4202119851. Data sources: MEDLINE, CINAHL, PsycINFO and Scopus databases were searched in August 2020 for primary research articles published in English, with no date limits applied. Articles were screened and reviewed independently by two researchers, and quality appraisal was conducted following the Mixed-Methods Appraisal Tool (2018). Results: The search retrieved 5985 articles; 23 articles satisfied eligibility criteria, consisting of mixed-methods ( n = 5), qualitative ( n = 7), quantitative descriptive ( n = 8) and quantitative non-randomised studies ( n = 3). Through data analysis, three key themes were identified: (1) Broadening the traditional role, (2) Understanding patient wishes and (3) Supporting families. Conclusions: Paramedics are a highly skilled workforce capable of helping to deliver palliative and end-of-life care to people in their homes and reducing avoidable hospital admissions, particularly for palliative emergencies. Future research should focus on investigating the efficacy of palliative care clinical practice guideline implementation for paramedics, understanding other healthcare professionals' perspectives, and undertaking health economic evaluations of targeted interventions.